Penerapan Budaya Sekolah 5S dalam Meningkatkan Karakter Cinta Damai Peserta Didik SMPN 7 Kota Serang - Ida Fitri Yani; Nur Khoirunnisa; Nelita Alpira Sapira; Wahyu Puji Rahayu Ningsih; Alfinda Adelia Dirli; Raina Hazleen Noor S; Citra Anggraeni (Universitas Palan, 2025)
The Indonesian educational system relies heavily on character education to meet the demands of the contemporary world. The 5S culture (Smile, Greeting, Greeting, Polite, Courteous) is a good technique to mold kids' character. This curriculum seeks to instill in children a disciplined, courteous, and peaceful mindset. Being ability to make people feel at ease and welcomed is a sign of a tranquil personality. This research was carried out at SMP Negeri 7 Kota Serang, which continuously applies the 5S culture to lessen bullying and improve student-to-student social contact. The 5S culture has been demonstrated to enhance kids' social awareness, discipline, tolerance, and friendship. This research employs a descriptive qualitative methodology, gathering data through recording and observation to investigate the application of the 5S culture. The results demonstrate the importance of the 5S culture in fostering a good and peaceful learning environment, promoting good behavior in students' daily lives, and lowering bad occurrences like bullying.